Exploring the musical counterparts of Mandarin tones to develop an innovative approach to teach Mandarin tones. - Wei, Han (2015)
Abstract Tones which are considered as an essential part of Mandarin pronunciation, seem to be challenging for second language learners to acquire. The current teaching methods do not illustrate the features of Mandarin tones clearly. Therefore, the purpose of this quantitative study is to investigate the musical counterparts of Mandarin tones in order to develop an innovative method which employs music to illustrate the pitch features of Mandarin tones. Participants included 10 native Mandarin speakers evenly distributed by gender who are qualified in Mandarin oral proficiency. They were recorded reading 20 monosyllable words with the four Mandarin tones equally distributed amongst the stimuli. The recordings were analysed by a computer software Praat. The fundamental frequency (F0) of each tone derived by Praat were then transformed into musical intervals (MIs). In this study, the average MIs of each Mandarin tone were extracted which not only illustrate the pitch information of each tone but also describe the relationships between the tones. Moreover, it is found that there is not a significant difference in terms of MIs of tones between the female and male group. Another finding is that there are no relative stable intervals across different individuals. Additionally, the 5-level scale generated in this study showed considerable differences to Chao’s (1948) scale which is widely used in teaching. According to the results of this iii study, a teaching method that utilises the musical notes generated from the MIs in this study is then developed.